Updated checklist of caddisflies (Insecta: Trichoptera) from the state of Piauí, Northeast Brazil, including a new species and new geographical records - Moreno, Lucas A.s.; Desidério, Gleison Robson; de Souza, Wagner Rafael M.; Lima, Lucas R.c. (Zootaxa, 2020)
Some regions, such as the Northeast Region of Brazil, are still severely understudied and the trichopteran fauna of this region is not entirely known, mainly in areas from Cerrado and Caatinga biomes. Currently, 25 species have been reported from Piauí State, but most of these records are concentrated from one locality. This study aimed to update the knowledge of Trichoptera diversity in this state, including the description of a new species and new geographic records for the Northeast region and Brazil. The samples were collected in seven municipalities, using various traps. Specimens were also received from the municipality of Bom Jesus. Thirty-two species were added for Trichoptera fauna of Piauí, 14 of these represent new records for Northeast Brazil; furthermore, Neotrichia palma Flint 1982 is a new record for Brazil. Additionally, a new species, Cernotina longa sp. nov., is describe and illustrate, being the third nominal record of the genus for the Caatinga biome. Thus, with the contribution of this study, 57 species, 20 genera and seven families of caddisflies are known for Piauí State.